Neuromuscular and perceptual-cognitive response to 4v4 small-sided game in youth soccer players - Skala, Filip; Zemková, Erika (Frontiers in Physiology, 2023)
The physical and psychological load of small-sided games (SSGs) can affect players’ neuromuscular and cognitive functions. Yet, little is known about the acute performance changes after such a specific exercise in young soccer players and their association with exercise load applied. This study investigates i) the neuromuscular and perceptual-cognitive response to the SSG exercise load, and ii) the relationship between pre- and post-SSG changes in variables of performance and the respective exercise load in youth soccer players. Sixteen participants (13.6±0.5y) underwent a 30-min SSG 4v4 + GK protocol. Prior to and after the SSG they performed countermovement jump (CMJ), planned and reactive Y-shaped agility tests (PA, RA), and go/no-go task (GNG). Their subjective perception of fatigue was evaluated by visual analog scale. Fatigue induced by SSG (perception of fatigue increased by 41.56%, p=.001, g=4.15) increased PA time (4.04%, p=.002, g=.97), RA time (6.45%, p=.003, g=1.16), and number of errors in the response inhibition task (87.1%, p=.023, rc=.57), whilst decreased CMJ height (−6.65%, p=.014, g=.56). These performance deteriorations were not significantly associated with neither internal nor external load variables. However, a less pronounced drop in performance was related to external load variables, i.e., ∆CMJ height and ∆RA time correlated with very high-speed running (rs=.66, p=.006; rs=−.50, p=.022; respectively) and maximal speed (r=.54, p=.032; r=−.52, p=.037; respectively), whilst ∆PA time was associated with high-intensity accelerations (rs=−.76, p=.002). These findings indicate that fatigue induced by SSG affects both planned and reactive agility, decision-making in response inhibition task, and explosive strength in youth soccer players regardless of significant contribution of any robust internal or external load variables. Nonetheless, high-intensity actions within SSG partially compensate for the decrements in their agility performance and explosive strength. The load variables encountered during SSG do not fully reflect youth players’ neuromuscular and perceptual-cognitive responses to sport-specific exercise.